2018
DOI: 10.1108/tg-02-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the continued use of e-government websites by citizens

Abstract: Purpose The concept of eGovernment has received much focus and emphasis across the public administrative sector, with interest centred on its public performance in terms of effectiveness and efficiency. Accordingly, this paper aims to consider those factors affecting the continuous adoption of eGovernment websites by citizens in the context of Jordan, through the design and development of a conceptual model, five factors included, notably digital literacy, e-service marketing efficiency, e-service quality, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
3
14
0
1
Order By: Relevance
“…The findings of the study provide strong support for the AC in determining the e-government continuance intention of citizens. Our findings are in line with those of Nawafleh (2018), which also indicate the role of public staff assistance in the continued use of e-government. For a developing country like India, where the under-skilled people need support for using e-governments services, the role of CSCs is pivotal in determining the e-government usage behaviour of citizens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of the study provide strong support for the AC in determining the e-government continuance intention of citizens. Our findings are in line with those of Nawafleh (2018), which also indicate the role of public staff assistance in the continued use of e-government. For a developing country like India, where the under-skilled people need support for using e-governments services, the role of CSCs is pivotal in determining the e-government usage behaviour of citizens.…”
Section: Discussionsupporting
confidence: 90%
“…Their findings suggest that SyQ, user satisfaction and habit are the most significant influencers of citizens’ continuance usage intention of e-filing. Nawafleh (2018) studied the continued use of e-government websites by Jordanian citizens, through e-service quality, digital literacy, compulsory e-service utilization, e-service marketing efficiency and public staff assistance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Por otra parte, las investigaciones (Hariguna et al, 2017;Nawafleh, 2018) indican que en la actualidad el número y/o cantidad de sitios web de e-gobierno, deben ir día con día en aumento, por lo cual se puede establecer que, sí el ciudadano no encuentra de primera instancia el servicio que requiere su percepción le hará pensar que los demás existentes no le son útiles, en ese sentido, expertos en el ámbito del desarrollo de software y aplicaciones web, explican que en cuanto más servicios estén digitalizados, mayor será el número de individuos que si integren al uso de los servicios de forma digital, ya que se perciben mayores ventajas al existir la integración de la mayoría de servicios a los sitios web (Alcaraz-Quiles, et al, 2018;Byun y Finnie, 2010;Singh, et al, 2016).…”
Section: Estudios De E-gobiernounclassified
“…Digital literacy Previous research showed influence of digital literacy in the context of digital government implementations [Nawafleh, 2018]…”
Section: Rq3mentioning
confidence: 99%